A Case Report : Pomerinarian mix dog poisoning ten months old due to rat poison - Abd Muhsi, Ach Moh (Journal of Veterinary and Animal Sciences; Vol 6 No 1 (2023)DO - 10.24843/JVAS.2023.v06.i01.p01, 2023)
A dog with a brown Pomeranian mix breed named Roni with female sex aged 10 months and weighing 8 kg, came to the Prema Vet Care clinic in Dalung on September 2, 2021 at 12 pm with complaints of hypersalivation, weakness, nausea, decreased appetite, the body feels hot, the dog is recorded to be fully vaccinated and has dewormed medicine, with maintenance around the house or not being released outside the home, and on September 3, 2021 the dog experienced vomiting after being given 4 tablets of norit tablets which work oas absorbents to absorb toxins, the first treatment was the administration of fluids infusion, injection of antibiotics and vitamins B1 and K1, it is suspected that the dog was poisoned byrat poison because the owner himself put a lot of mouse traps in the form of food mixed with rat poison (rodentox) around his house. Rodentox is a second generation rodenticide, this poison contains the active ingredient bromadiolone plus nitrite poison. Based on the anamnesis, clinical examination, and blood tests, the dog was diagnosed as having been poisoned by rat poison with a Fausta prognosis. For the first treatment, the dog was given the antibiotic betamox (0.8 ml), vitamin B1 (Neurotropic®) injection at a dose of 0.8 ml, prednisone 5 mg (40 tabs pulv.bd.d for 14 days), ciprofloxacin 500 mg (2 tabs pulv .bd.d for 7 days), and vitamin K1 (7.5 tab pulv.bd.d for 7 days) and the dog improved during 7 days of therapy and the clinical symptoms experienced had decreased.